OP0084 Cardiopathogenic Role of Human RO/SSA and LA/SSA Antibodies Demonstrated in a Novel Animal Model of Congenital Heart Block. (23rd January 2014) - Hoxha, A.; Ruffatti, A.; Ottosson, V.; Ottosson, L.; Hedlund, M.; Del Ross, T.; Punzi, L.; Sonesson, S.-E.; Wahren-Herlenius, M.
Abstract : Background: Congenital atrioventricular block (CHB) depend on Ro/SSA and/or La/SSB-autoantibody mediated inflammation and subsequent fibrosis of the atrioventricular node. Despite the association of maternal Ro/SSA and La/SSB autoantibodes with congenital heart block, the mechanisms involved remain unclear. Objectives: To study the effect on cardiac conduction of purified human IgG antibodies from a CHB patient mother in an animal model. Methods: Female Dark Agouti rats (Charles-Rivers, Germany), 15 weeks old, were injected intra peritoneally with different doses (4 and 2 mg) of IgG purified from a CHB mother tested positive for anti-Ro52-p200 antibodies, a healthy control or with vehicle only on day 7 post mating. The assessment of fetal cardiac function during pregnancy was performed by fetal echocardiography/Doppler recordings at approximately 14 days of pregnancy, and neonatal cardiac function after birth was assessed by ECG recordings within 24 h of birth. Results: Performing echocardiography/Doppler we observed significant bradycardia and AV time prolongation in the group injected with 4 mg patient IgG compared to pups injected with 4 mg control IgG or PBS (p=0.0004 and p=0.001, respectively) as well as a significant prolongation of isovolumetric contraction time (ICT) and ejection time (ET) time (p=0.01 and p=0.007). Furthermore, pups in the group injected with 4 mg patient IgG had a significantly higher myocardial performance index (MPI) (p=0.002) than the group injected with 4 mg control IgG. We did not observe bradycardia and/or prolongation of AV time in the group injected with 2 mg patient IgG. However, a significant prolongation of ICT, isovolumetric relaxation time (IRT) and ET time was observed also in the group injected with 2 mg patient IgG compared to 2 mg control IgG (p=0.0003, p=0.001 and p=0.03, respectively). Further, there was a significant increase of MPI (p=0.002) between groups injected with 2 mg patient and control IgG. The ECGs recordings showed that the pups from the group injected with 4 mg patient IgG present a significant reduction of mean heart rate compared to the group injected with 4 mg control IgG (p<0.0001). Moreover, the pups from the 4 mg patient IgG group present a significant prolongation of the PR and RR intervals compared to the group injected with 4 mg IgG control sera (p<0.0001). There was no bradycardia and/or prolongation of PR and RR interval in the group injected with 2 mg patient IgG. Conclusions: Our data suggest that high levels (4 mg) of Ro/SSA and La/SSA autoantibodies induce bradycardia, AV time prolongation and decrease cardiac performance, accurately mimicking features of the human disease and confirming a role for the autoantibodies in disease pathogenesis. Even at low levels (2 mg) these antibodies cause a decrease in cardiac performance. The data also suggest that an animal model for CHB can be established by a simple technique of passive transfer of human IgG from a patient with a child with CHB. This model will be useful and highly relevant for investigating the pathogenesis of CHB induced by human Ro/La antibodies, and for evaluating novel therapeutic approaches and drugs. Disclosure of Interest: None Declared